Synergy Between Bank Indonesia and the Maluku Government: Implementation of Philip Lesly’s Communication Model in Inflation Control - Kulwembun, Yohanes Brilian F.; Alfredo, Ronald; Waliulu, Yuniar Sakinah (Baileo: Jurnal Sosial Humaniora, 2024)
This study aims to describe the communication synergy between Bank Indonesia and the Maluku Provincial Government in controlling inflation through the implementation of Philip Lesley’s communication planning model. This synergy is manifested in the Regional Inflation Control Team (TPID) of Maluku, where Bank Indonesia acts as the Organizing Entity and the Maluku Provincial Government as the target public. This research uses a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings show that the communication synergy between the two institutions operates effectively through four planning stages: analysis and research, policy formulation, program planning, and communication activities. Additionally, the Maluku Provincial Government plays a role in providing feedback and evaluation through its involved Regional Government Organizations (OPD). The novelty of this research lies in the structured application of Philip Lesley’s communication model in the context of inflation control in Maluku, illustrating how strategic communication can strengthen inter-agency cooperation to achieve economic goals. The study concludes that successful inflation control in Maluku is highly dependent on targeted communication planning and clear role distribution between Bank Indonesia and the Maluku Provincial Government.